2020
DOI: 10.1111/adb.12985
|View full text |Cite
|
Sign up to set email alerts
|

Reduced frontostriatal functional connectivity and associations with severity of Internet gaming disorder

Abstract: Cognitive, functional, and structural brain factors involving frontal executive and striatal reward networks have been implicated in Internet gaming disorder (IGD). However, frontostriatal network connectivity and its association with addiction severity are poorly understood in IGD. Resting‐state fMRI data from 337 subjects (130 with IGD, 207 with recreational game use [RGU]) were collected. Striatal‐cortical communications were measured with resting‐state functional connectivity (FC) using coherent spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 64 publications
(146 reference statements)
2
16
0
Order By: Relevance
“…In contrast, higher levels of craving/social problems were associated with enhanced connectivity between the ventral striatum and the occipital, orbitofrontal and insular regions. Negative associations between loss of control and striatum connectivity might reflect dysregulations in inhibitory control and visual salience processing including the superior and middle occipital regions, and the action control system, including the cerebellum and ACC (Dong et al, 2021b; Meng, Deng, Wang, Guo, & Li, 2015). Positive associations between craving/social problems and the ventral striatal system encompassed occipital regions involved in visual salience processing and orbitofrontal regions involved in reward processing which have been associated with cue-reactivity and craving (Hanlon, Dowdle, Naselaris, Canterberry, & Cortese, 2014; Zhou et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, higher levels of craving/social problems were associated with enhanced connectivity between the ventral striatum and the occipital, orbitofrontal and insular regions. Negative associations between loss of control and striatum connectivity might reflect dysregulations in inhibitory control and visual salience processing including the superior and middle occipital regions, and the action control system, including the cerebellum and ACC (Dong et al, 2021b; Meng, Deng, Wang, Guo, & Li, 2015). Positive associations between craving/social problems and the ventral striatal system encompassed occipital regions involved in visual salience processing and orbitofrontal regions involved in reward processing which have been associated with cue-reactivity and craving (Hanlon, Dowdle, Naselaris, Canterberry, & Cortese, 2014; Zhou et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The first finding extends our understanding of a cortical neurodevelopmental component of SPA in individuals without any psychiatric disorder according to ICD‐10 or DSM‐5 in manifold ways: First, SFG plays a crucial role in higher cognitive functions (e.g., working memory) (Boisgueheneuc et al., 2006), executive control over reward processes (Dong et al., 2021), introspection (Goldberg et al., 2006), and complex motor tasks (W. Li et al., 2013; Thomann et al., 2015). In particular, introspection is a process of perceiving or being aware of own thoughts and feelings (Batali, 1983) and hence, it is significantly impaired in addiction disorders, leading to lower awareness of the disease, lack of motivation to change behavior and to look for appropriate treatment options (Goldstein & Volkow, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…Of particular importance for the understanding the function of SFG in SPA is its anatomical connection to the supplementary motor area, a region that is responsible for preparation, initiation, and monitoring of an action (Wolf et al, 2008). These findings are remarkable, given that decreased functional connectivity between SFG and basal ganglia is also involved in IGD (Dong et al, 2021). Further, if an individual wants to stop its excessive smartphone use behavior, it needs to cognitively decide to not use the smartphone.…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in the IFC and DLPFC are thought to be directly related to uncontrolled drug abuse (Ely et al, 2020;Qian et al, 2020), and the stimulation of these regions was demonstrated to be effective in relieving addictive symptoms (Chen et al, 2020b;Newman-Norlund et al, 2020). In IA, a close association between the dysfunction of IFC and DLPFC and the uncontrolled online playing has also been demonstrated (Dong et al, 2020). Although the AG is not typically associated with executive control function, the crucial role of the AG in inhibition control has been well demonstrated by previous studies (Castelluccio et al, 2014;Nobusako et al, 2017;Lewis et al, 2019).…”
Section: Hypoactive Reflecting Systemmentioning
confidence: 86%